Pengajaran Keterampilan Membaca Bahasa Arab di Madrasah Aliyah; Permasalahan dan Alternatif Pemecahannya - Fahrur Rosikh; Nashihin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2020)
In accordance with what has been stipulated in the Regulation of the Minister of Religion of the Republic of Indonesia that Arabic language subjects are subjects that are directed to encourage, guide, develop, and foster abilities and foster a positive attitude towards Arabic, both receptively and productively. Reading skills (maharah al-qiro'ah) in learning Arabic at Madrasah Aliyah are one of the four basic language skills that must be taught by teachers and mastered by students. The method used in this research is descriptive qualitative method that seeks to collect as much information as possible through documentation, interviews, and observations to be further studied and analyzed and draw the final result in the form of conclusions. The results obtained are the reality in the field shows that the teaching of language reading skills Arabic is done by the teacher not everything goes well, in fact there are still many problems that result in learning objectives cannot be achieved. Therefore, teachers need to understand and master various important aspects of teaching reading skills so that teaching activities can run well and the stated teaching goals can be achieved.